If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y = 12(y + 12) Reorder the terms: 13y = 12(12 + y) 13y = (12 * 12 + y * 12) 13y = (144 + 12y) Solving 13y = 144 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 13y + -12y = 144 + 12y + -12y Combine like terms: 13y + -12y = 1y 1y = 144 + 12y + -12y Combine like terms: 12y + -12y = 0 1y = 144 + 0 1y = 144 Divide each side by '1'. y = 144 Simplifying y = 144
| 12x+60=30 | | 9(42)-9(4)= | | .66(9x-3)=-4+8x | | 10x-8=6x+10 | | 15-10y=27-3y+9 | | 7a-2=5 | | 5b=-75 | | 4a+5=9a | | 4(1-x)+3=-2(x+1) | | X-29=-86 | | 7(c-7)=6(4+c) | | 5(3m+1)-8(2m+3)= | | 48=9x-18 | | 7-3(4x+1)=5x-13 | | 4(2x+8)=-17+41 | | -2x-3=6x+4 | | -3y+9=15y-9 | | 5(45+5)= | | 1+8m=6m-5 | | 3=2x+10 | | t^2+14t+49=0 | | (2w-3)2-2(2w-3)-15=0 | | 6x+1=2x+13 | | [6y-2]+4=22 | | 15+0.50pm=25+0.25pm | | [6y-2]+4= | | 6x-5=8x-9 | | 3x+23=4x | | 4a=-24 | | 2w-2=40 | | 8x+2=7x+6 | | 9(x+1)=-3x+5(x+2) |